1998
DOI: 10.1038/sj.ejcn.1600571
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of an elevated resting energy expenditure in patients with chronic obstructive pulmonary disease in relation to body composition and lung function

Abstract: Objective: This study describes the prevalence and characteristics of an elevated resting energy expenditure (REE) in patients with chronic obstructive pulmonary disease (COPD). Design and setting: Patients were consecutively admitted to an in-patient pulmonary rehabilitation centre. Subjects: The study group consisted of 172 (123<) clinically stable patients with COPD, age mean (s.d. ) 64 (10) y). Interventions: REE was assessed by indirect calorimetry (ventilated hood) and adjusted for the in¯uence of fatfre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
1
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 36 publications
5
68
1
6
Order By: Relevance
“…Patients with COPD have been reported to have a raised BMR ( $ 10%), partly because of an increase in the energy cost of breathing (Creutzberg et al, 1998). However, there is no universal agreement on this issue, since Ryan et al found no increase in BMR in malnourished patients with COPD (Ryan et al, 1993).…”
Section: Introductionmentioning
confidence: 62%
“…Patients with COPD have been reported to have a raised BMR ( $ 10%), partly because of an increase in the energy cost of breathing (Creutzberg et al, 1998). However, there is no universal agreement on this issue, since Ryan et al found no increase in BMR in malnourished patients with COPD (Ryan et al, 1993).…”
Section: Introductionmentioning
confidence: 62%
“…This underestimation is not surprising given that some subjects with moderate to severe COPD have been demonstrated to have increased resting and total daily EE and a greater oxygen consumption for a given workload compared to normal subjects (30). This can be attributed to reductions in skeletal muscle efficiency (31) and a higher work of breathing at a given level of ventilation likely not captured by accelerometers.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, increased oxygen cost for respiratory muscles during rest and exercise as well, and their impact on malnutrition have often been emphasized in COPD (Baarends et al, 1997;Creutzberg et al, 1998;Congleton 1999). Even more, earlier data have demonstrated that lung function impairment and augmented ventilation are correlated in both restrictive and obstructive lung diseases (Sridhar et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, we found a previously undescribed correlation between FFMI and P 0.1 as a non-invasive marker of inspiratory drive. Of course, measurements of energy expenditure are necessary to confirm the impact of respiratory mechanics on nutritional status (Creutzberg et al, 1998). Further, it cannot be excluded, however, that dyspnoea, which worsens with increasing severity of disease, has prevented adequate caloric intake (Congleton 1999, Tang et al, 2002.…”
Section: Discussionmentioning
confidence: 99%